Levetiracetam as an alternative therapy for Tourette syndrome - MA Martínez-Granero; A García-Pérez; F Montañes (Neuropsychiatric Disease and Treatment, 2010)
MA Martínez-Granero, A García-Pérez, F MontañesDepartment of Pediatrics and Psychiatry, Hospital Universitario Fundación Alcorcón, Madrid, SpainAbstract: Tourette syndrome is a common childhood-onset neuropsychiatric disorder characterized by chronic tics and frequent comorbid conditions such as attention deficit disorder. Most currently used tic-suppressing drugs are frequently associated with serious adverse events. Thus, alternative therapeutic agents with more favorable side-effect profiles are being evaluated. New hypotheses and recent studies involving GABAergic system in the pathophysiology of Tourette syndrome suppose a reason for the evaluation of GABAergic drugs. Levetiracetam is a drug with an atypical GABAergic mechanism of action that might be expected to improve tics. Although trials performed to evaluate the efficacy of levetiracetam in the treatment of Tourette syndrome have provided conflicting results, it may be useful in some patients. The established safe profile of levetiracetam makes this drug an alternative for treatment if intolerance to currently used drugs appears, but additional evaluation with larger and longer duration controlled studies are necessary to assess the real efficacy in patients with Tourette syndrome.Keywords: Tourette syndrome, levetiracetam, tics, children, adolescents, GABA